Validated stability indicating HPLC method for estimation of theophylline from a novel microsphere formulation - Shidhaye, Supriya; Malke, Sheetal; Kadam, Vilasrao (Asian Journal of Pharmaceutics (AJP), 2014)
A new, simple, specific, precise and robust isocratic reversed-phase (RP) stability-indicating high-performance liquid chromatographic (HPLC) method was developed and validated for determination of theophylline from a novel formulation. The liquid chromatographic separation was achieved isocratically using a mobile phase of acetonitrile: 50 mM sodium acetate buffer (15:85) adjusted to pH 6.5 using dilute hydrochloric acid. The analysis was carried out using Hi-Q-Sil C18 column [250 mm x 4.6 mm, 5 Î¼m] at flow rate of 1 ml/min and the UV detection at 270 nm. The method was validated for accuracy, precision, linearity, range, selectivity, and robustness. The linearity of the proposed method was investigated in the range of 1 to 24 Î¼g/ml (r2 = 0.9995). The drug was subjected to oxidation, hydrolysis, heat, and photolysis to apply stress conditions. The method provided good peak parameters with retention time of 8.6 Â± 0.3 min. Degradation products resulting from stress studies did not interfere with the detection of theophylline and the assay can thus be considered as stability-indicating.